The Effect of Hydrodynamics on Mass Transfer and Reactive Absorption of CO2 in Rotating Packed Bed - Zahir, Abdul (Curtin University, 2023)
This study numerically investigates the absorption efficiency of rotating packed bed (RPB) for CO2 using monoethanolamine (MEA). The absorption efficiency of the RPB depends on the hydrodynamics of MEA in RPB and the chemical reaction between MEA and CO2. Therefore, the hydrodynamics and chemical reaction were optimized for enhanced CO2 absorption. The study exhibits that the optimized conditions can increase the CO2 absorption up to 8 and 2.3 times for physical and chemical absorption, respectively.